Correlates of job satisfaction among female non-academics - Lokmanalhakim, Liana Nabiha; Hasbullah, Muslihah (Human Resource Management Academic Research Society, 2022)
This study aims to determine the relationship between motivation, emotional intelligence and job satisfaction among female non-academics in Universiti Putra Malaysia (UPM). A total of 154 respondents were involved in the study. A self-administered questionnaire was used in the data collection. Result revealed that respondents had high levels of extrinsic motivation, intrinsic motivation, emotional intelligence and job satisfaction. Extrinsic motivation (r = 0.33, p < 0.01), intrinsic motivation (r = 0.44, p < 0.01) and emotional intelligence (r = 0.48, p < 0.01) were significantly correlated with job satisfaction. There was also a significant difference in job satisfaction between marital status, (F (2,150) = 8.16, p < 0.05), where the divorced female respondents exhibited higher job satisfaction than the single and married female respondents. Multiple regression analysis revealed that intrinsic motivation (? = 0.22, p < 0.05) and emotional intelligence (? = 0.31, p < 0.001) were the significant predictors of job satisfaction. Respondents’ intrinsic motivation and emotional intelligence were important in influencing job satisfaction. Thus, by understanding the positive impact of motivation and emotional intelligence towards job satisfaction among female non-academics, it helped to ensure the high quality of job satisfaction while maintaining the performance of higher learning institutions in Malaysia.